2001
DOI: 10.1210/en.142.11.4818
|View full text |Cite
|
Sign up to set email alerts
|

Effect of IL-6 on IGF Binding Protein-3: A Study in IL-6 Transgenic Mice and in Patients with Systemic Juvenile Idiopathic Arthritis

Abstract: Stunted growth is a common complication of childhood diseases characterized by chronic inflammation or infections. We previously demonstrated that NSE/hIL-6 transgenic mice, overexpressing the inflammatory cytokine IL-6 since early phase of life, showed a marked growth defect associated with decreased IGF-I levels, suggesting that IL-6 is one of the factors involved in stunted growth complicating chronic inflammation in childhood. Here we show that NSE/hIL-6 mice have normal liver IGF-I production, decreased l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
100
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(107 citation statements)
references
References 0 publications
7
100
0
Order By: Relevance
“…In agreement with an in vitro observation showing no effect of IL-6 on GH-induced IGF-I mRNA expression in cultured hepatocytes [14], we found that IGF-I protein levels in liver extracts were similar in transgenic NSE/hIL-6 mice and in non-transgenic littermates [15]. Taken together, these observations exclude a direct effect of IL-6 overexpression on liver IGF-I production, and show that the decrease in circulating IGF-I levels in NSE/hIL-6 mice cannot be explained by low liver IGF-I production.…”
Section: Abnormalities Of the Insulin-like Growth Factor-i System In supporting
confidence: 92%
“…In agreement with an in vitro observation showing no effect of IL-6 on GH-induced IGF-I mRNA expression in cultured hepatocytes [14], we found that IGF-I protein levels in liver extracts were similar in transgenic NSE/hIL-6 mice and in non-transgenic littermates [15]. Taken together, these observations exclude a direct effect of IL-6 overexpression on liver IGF-I production, and show that the decrease in circulating IGF-I levels in NSE/hIL-6 mice cannot be explained by low liver IGF-I production.…”
Section: Abnormalities Of the Insulin-like Growth Factor-i System In supporting
confidence: 92%
“…An association between IL-6 and IGFBP-3 proteolysis was expected since IL-6 transgenic mice have increased IGFBP-3 proteolysis [18]. In addition, several states characterized by increased IGFBP-3 proteolysis, e.g., the post-operative state [21], exercise [22], critical illness [24, 25], type 2 diabetes [19], and arthritis [18] have elevated levels of IL-6 [12, 13, 20, 23, 25].…”
Section: Resultsmentioning
confidence: 99%
“…IL-6 has been shown to reduce GH sensitivity in mice [49]. In vivo experiments with mice over-expressing IL-6 have shown unchanged [18] or reduced [49] IGF-I expression in the liver. In our study, total IGF-I concentrations were not changed by an IL-6 infusion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a transgenic mouse model, De Benedetti et al [17, 18] have suggested that IL-6 may be part of the mechanism by which chronic inflammation inhibits growth. Thus, overexpression of IL-6 was followed by reduced plasma IGF-I and longitudinal growth, without influence on liver IGF-I production.…”
Section: Introductionmentioning
confidence: 99%